PERBANDINGAN PENGATURAN PENYALAHGUNAAN POSISI DOMINAN OLEH BIG TECH COMPANY DALAM PASAR DIGITAL DI INDONESIA DAN JERMAN: Comparison of Regulations On Abuse Of Dominant Positions By Big Tech Companies in Indonesia and Germany’s Digital Market - Michelle Kwok; Dian Purnamasari (Reformasi Hukum Trisakti, 2026)
The development of the digital economy has introduced new challenges in competition law, particularly concerning the abuse of dominant positions by Big Tech companies that control digital markets through data dominance, algorithms, and network effects. The research question in this study concerns the similarities and differences between Indonesian and German regulations on the abuse of dominant positions by Big Tech companies in digital markets. The research method applied is normative legal research with a comparative approach. The findings indicate that Indonesia, through Law No. 5 of 1999, still assesses dominant positions based on conventional market share, whereas Germany, through the Gesetz gegen Wettbewerbsbeschränkungen (GWB), has introduced specific provisions such as Sections 18(3a) and 19a that take into account the characteristics of digital markets, including multi-sided markets, network effects, and data access. In conclusion, Germany’s regulatory framework is more adaptive, comprehensive, and capable of anticipating abuses of dominance by Big Tech companies, while Indonesia still requires regulatory updates to align with the dynamics of the global digital market.